Teacher preparation as interruption or disruption? Understanding identity (re)constitution for critical inclusion. (May 2019) - Siuty, Molly Baustien
Highlights: New teachers demonstrated only a partial disruption of dominant ideologies. Identities of resistance drew on Disability Studies in Education frameworks. Identities of reification perpetuated ableism and justified exclusion. Teacher preparation must address tensions between special and inclusive education.